ANALYSIS OF MULTI-STRAIN BARTONELLA PATHOGENS IN NATURAL HOST POPULATION — DO THEY BEHAVE AS SPECIES OR MINOR GENETIC VARIANTS - HOSOLY, P.; TEGNE, D. (International Journal of Multidisciplinary Research and Studies, 2021)
Modern advances in genetic analysis have made it feasible to determine the variant form of a pathogen infecting a bunch. Classification of pathogen variants is usually performed by clustering analysis of the observed genetic divergence among the variants. A natural question arises whether the genetically distinct variants are epidemiologically distinct. A broader question is whether or not the various variants constitute separate microbial species or represent minor variations of the identical species. These important issues were addressed within the context of analyzing the dynamics of genetically distinct variants of Bartonella bacteria in gnawing animal hosts. Frequencies of acquiring a brand new variant were measured about the genetic differences between variants successively infecting a private rodent host. Two statistical techniques were introduced for performing such analysis, and also the methodologies were illustrated with a collection of information collected from a specific multi-strain Bartonella system. We dole out a frequency analysis of co-infection patterns and a Markoff chain analysis of panels of successive mixed infection statistics for testing some particular gene-based grouping of the Bartonella variants with a panel of observed disease data from a rodent population. Our analysis suggests that the three genogroups A, B, and C of Bartonella function as independent species but the variants within each genogroup enjoy some cross-immunity against one another. The newly developed methodologies are broadly applicable for analyzing other multi-strain pathogen data which are increasingly collected for diverse infectious diseases.